NEXT-GENERATION SEQUENCING IN PEDIATRIC ACUTE LYMPHOBLASTIC LEUKEMIA - Klementina Črepinšek; Maruša Debeljak; Janez Jazbec (Slovenska pediatrija, 2021)

(untitled)
Genetically, acute lymphoblastic leukaemia (ALL) is a very heterogeneous disease, but it has also been one of the most thoroughly researched diseases. Nevertheless, our knowledge of how genetic changes are interrelated in the development of leukaemia and treatment resistance is still lacking. Certain ALL subtypes still have extremely poor treatment outcomes, with up to 20% of patients experiencing a relapse, the majority of whom do not survive. New approaches in the diagnostic work-up for ALL, based on the use of next-generation sequencing methods, have provided new possibilities for expanding our understanding of the development of the disease biology, identification of new genetic subtypes, and better risk assessment. They also enable monitoring of clonal dynamics during treatment and at relapse, which opens up new prospects for better management of patients with ALL relapses. There are also attempts to use these methods for more accurate monitoring of treatment response and identification of new potential targets for more focused treatment.